2015
DOI: 10.1146/annurev-psych-010814-015214
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual Learning: Toward a Comprehensive Theory

Abstract: Visual perceptual learning (VPL) is long-term performance increase resulting from visual perceptual experience. Task-relevant VPL of a feature results from training of a task on the feature relevant to the task. Task-irrelevant VPL arises as a result of exposure to the feature irrelevant to the trained task. There are at least two serious problems. First, which stage of information processing is changed in association with task-relevant VPL is controversial. Second, no model has ever explained both task-releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
282
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 287 publications
(299 citation statements)
references
References 153 publications
(281 reference statements)
16
282
1
Order By: Relevance
“…The perceptual learning literature, which is the main paradigm for studying adult sensory plasticity, suggests that long term plasticity effects are more prominent in associative areas (13,18), questioning the original idea that V1 circuitry can be optimized by perceptual experience (15). Our paradigm is very different from perceptual learning, having short-term consequences and being independent of perceptual decisions; our data clearly show that V1 circuitry can change with abnormal visual experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The perceptual learning literature, which is the main paradigm for studying adult sensory plasticity, suggests that long term plasticity effects are more prominent in associative areas (13,18), questioning the original idea that V1 circuitry can be optimized by perceptual experience (15). Our paradigm is very different from perceptual learning, having short-term consequences and being independent of perceptual decisions; our data clearly show that V1 circuitry can change with abnormal visual experience.…”
Section: Discussionmentioning
confidence: 99%
“…Perceptual learning requires long training sessions repeated over several days in combination with positive reward (13)(14)(15)(16)(17)(18). In spite of extensive research, it is still debated whether perceptual learning fine-tunes the neuronal responses at level of primary visual cortex or whether the effect primarily lies in associative cortices (18)(19)(20)(21)(22)(23)(24), which usually retain a higher level of plasticity in adulthood. More recently, psychophysical studies have revealed a form of adult plasticity after short-term deprivation, probably associated with an alteration of primary visual cortex processing, where deprivation paradoxically leads to enhanced sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…perceptual learning | motion | psychophysics | transcranial magnetic stimulation | functional magnetic resonance imaging P erceptual learning, an enduring improvement in the performance of a sensory task resulting from practice, has been widely used as a model to study experience-dependent cortical plasticity in adults (1). However, at present, there is no consensus on the nature of the neural mechanisms underlying this type of learning.…”
mentioning
confidence: 99%
“…Our participant group of children with IN consisted of children with idiopathic IN and children with albinism accompanied by IN. Previous studies have demonstrated that reading performance can be improved by perceptual learning, [18][19][20] which refers to a long-term performance increase resulting from perceptual experience. 21 The reading measure that is improved by perceptual learning depends on the paradigm used. Visual span training, which aims to increase the number of letters that can be read without moving the eyes (visual span) by training several locations in the visual field, can increase maximum reading speed by an impressive 41%.…”
mentioning
confidence: 99%